IMPACT OF INTERNAL FACTORS ON FINANCIAL PERFORMANCE OF IDX CONSUMER NON-CYCLICAL SECTOR - Suherman, Jovanny Mudita; Susilawaty, Lilis (Jurnal Akuntansi Bisnis, 2026)
Background: The uncertainty of global and national economic conditions requires companies to maintain strong financial performance. The consumer non-cyclical sector is generally considered as counter cyclical, however evidence shows that it is still affected by economic fluctuations.Objective: This study analyzes the influence of internal factors on the financial performance of companies in the consumer non-cyclical sector listed on Indonesia Stock Exchange during period 2020-2024. By examining the internal factors, companies can enhance their financial performance.Research Methods: Population in this study consist of consumer non-cyclical sector listed on Indonesia Stock Exchange 2020-2024. Purposive sampling as the sampling technique resulting 63 companies selected to analyzes. Software for data processing is EViews 13 to test the research hypotheses, meanwhile data analysis techniques are panel data regression, simultaneous testing, partial testing, and coefficient of determination. Fixed Effect Model and Random Effect Model are used as model of panel data regression for analyzing ROE and EPS.Research Results: The results show that net working capital has significant effect on EPS, while financial leverage significantly influences ROE. Firm size, operational efficiency, and liquidity do not have significant influences on ROE and EPS. Simultaneously all independent variables collectively affect the dependent variables representing financial performance. Recommended for company management to optimize the use of net working capital efficiently to improve EPS and manage financial leverage at a balanced level to avoid placing burden on company’s finances.Originality/Novelty of Research: The study provides insight for companies to manage and evaluate the internal factors that affect financial performance. This study also support trade-off theory of capital structure and provide insight for investor about signaling.